1985
DOI: 10.3109/15513818509025906
|View full text |Cite
|
Sign up to set email alerts
|

Structural Abnormalities of the Myenteric (Auerbach's) Plexus in Familial Dysautonomia (Riley-Day Syndrome) as Demonstrated by Flat-Mount Preparation of the Esophagus and Stomach

Abstract: The esophageal and gastric myenteric (Auerbach's) plexus were studied by a flat-mount preparation in 3 patients with familial dysautonomia. In 1 patient a typical esophageal network was found in the stomach. In another patient both esophageal and gastric plexus patterns were significantly different from normal. These changes, by producing abnormal nervous stimulation, may explain disturbed motility of the esophagus and stomach in familial dysautonomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…While it is well known that FD patients suffer from frequent GI dysfunction 17 , at least one imaging study found delayed esophageal transit times and delayed gastric emptying among FD patients compared to healthy control subjects, implicating a dysfunctional myenteric plexus of the upper GI tract in FD 42 . These results are consistent with two case studies that isolated and visually compared the esophageal, gastric and/or appendiceal myenteric plexus of FD patients and age-matched control subjects 43 ; these studies showed significant reductions in the neuronal number and/or ganglion complexity. Collectively, these results suggest that dysfunctional gut motility in FD patients is most likely due to alterations in neuronal density throughout the GI tract.…”
Section: Discussionsupporting
confidence: 90%
“…While it is well known that FD patients suffer from frequent GI dysfunction 17 , at least one imaging study found delayed esophageal transit times and delayed gastric emptying among FD patients compared to healthy control subjects, implicating a dysfunctional myenteric plexus of the upper GI tract in FD 42 . These results are consistent with two case studies that isolated and visually compared the esophageal, gastric and/or appendiceal myenteric plexus of FD patients and age-matched control subjects 43 ; these studies showed significant reductions in the neuronal number and/or ganglion complexity. Collectively, these results suggest that dysfunctional gut motility in FD patients is most likely due to alterations in neuronal density throughout the GI tract.…”
Section: Discussionsupporting
confidence: 90%
“…It should be noted that our conclusions are based on observations on the appendix because specimens of upper gastrointestinal tract from FD patients are not available. However, our results are in accordance with a study on the esophagus and stomach from FD patients [18], and are thus likely to represent, at least qualitatively, other regions of the digestive system.…”
Section: Discussionsupporting
confidence: 93%
“…Two studies, each on a single patient, revealed no histological changes in myenteric neurons [20,22], and in another work on a single patient, some abnormalities in these neurons were noticed [21]. The most recent study dealing with the innervation of the gastrointestinal tract of FD patients was published back in 1985 [18]. In that study, which included only three patients, two patients demonstrated morphologic differences of the esophageal and gastric myenteric plexuses, using flat mount preparations.…”
Section: Discussionmentioning
confidence: 97%
“…Abnormality in the relative numbers of different transmitter-secreting neurons in the This paper presents the results of preliminary studies of the structure of the Auerbach plexus in a variety of genetic disorders. Ariel and Wells, 1985;Nakazato et al, 19861. Weinberg, 1975;Emery et al, 1967;Ariel and Wells, 19851.…”
Section: Introductionmentioning
confidence: 99%